Cocoa flavanol consumption improves cognitive function, blood pressure control, and metabolic profile in elderly subjects: the Cocoa, Cognition, and Aging (CoCoA) Study--a randomized controlled trial - Mastroiacovo, Daniela; Kwik-Uribe, Catherine; Grassi, Davide; Necozione, Stefano; Raffaele, Angelo; Pistacchio, Luana; Righetti, Roberta; Bocale, Raffaella; Lechiara, Maria Carmela; Marini, Carmine; Ferri, Claudio; Desideri, Giovambattista (The American journal of clinical nutrition, 2015)
Recent evidence has indicated that flavanol consumption may have many health benefits in humans, including improved cognitive activities. The aim was to evaluate the effect of flavanol consumption on cognitive performance in cognitively intact elderly subjects. This was a double-blind, controlled, parallel-arm study conducted in 90 elderly individuals without clinical evidence of cognitive dysfunction who were randomly assigned to consume daily for 8 wk a drink containing 993 mg [high flavanol (HF)], 520 mg [intermediate flavanol (IF)], or 48 mg [low flavanol (LF)] cocoa flavanols (CFs). Cognitive function was assessed at baseline and after 8 wk by using the Mini-Mental State Examination (MMSE), the Trail Making Test (TMT) A and B, and the Verbal Fluency Test (VFT). The changes in MMSE score in response to the 3 different treatments were not different. In contrast, there was a positive impact of the intervention on specific aspects of cognitive function. Mean changes (±SEs) in the time required to complete the TMT A and B after consumption of the HF (-8.6 ± 0.4 and -16.5 ± 0.8 s, respectively) and IF (-6.7 ± 0.5 and -14.2 ± 0.5 s, respectively) drinks significantly (P < 0.0001) differed from that after consumption of the LF drinks (-0.8 ± 1.6 and -1.1 ± 0.7 s, respectively). Similarly, VFT scores significantly improved among all treatment groups, but the magnitude of improvement in the VFT score was significantly (P < 0.0001) greater in the HF group (7.7 ± 1.1 words/60 s) than in the IF (3.6 ± 1.2 words/60 s) and LF (1.3 ± 0.5 words/60 s) groups. Significantly different improvements in insulin resistance (P < 0.0001), blood pressure (P < 0.0001), and lipid peroxidation (P = 0.001) were also observed for the HF and IF groups in comparison with the LF group. Changes in insulin resistance explained ∼17% of changes in composite z score (partial r² = 0.1703, P < 0.0001). This dietary intervention study provides evidence that regular CF consumption can reduce some measures of age-related cognitive dysfunction, possibly through an improvement in insulin sensitivity. These data suggest that the habitual intake of flavanols can support healthy cognitive function with age.